2017
DOI: 10.1016/j.brs.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Neuronal Activity in the Motor Thalamus during GPi-DBS in the MPTP Nonhuman Primate Model of Parkinson's Disease

Abstract: Background The motor thalamus is a key nodal point in the pallidothalamocortical “motor” circuit, which has been implicated in the pathogenesis of Parkinson's disease (PD) and other movement disorders. Although a critical structure in the motor circuit, the role of the motor thalamus in mediating the therapeutic effects of deep brain stimulation (DBS) of the internal segment of the globus pallidus (GPi) is not fully understood. Objective To characterize the changes in neuronal activity in the pallidal (ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…). However, parkinsonism is associated with relatively minor changes in firing in the basal ganglia receiving portion of the thalamus . Whereas traditional models predict that interventions aimed at the basal ganglia–receiving portion of the ventral motor thalamus “should” impact bradykinesia or akinesia, these predictions have not been confirmed in parkinsonian animals or human patients with the disease (e.g., see an earlier work) .…”
Section: Evolving Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…). However, parkinsonism is associated with relatively minor changes in firing in the basal ganglia receiving portion of the thalamus . Whereas traditional models predict that interventions aimed at the basal ganglia–receiving portion of the ventral motor thalamus “should” impact bradykinesia or akinesia, these predictions have not been confirmed in parkinsonian animals or human patients with the disease (e.g., see an earlier work) .…”
Section: Evolving Topicsmentioning
confidence: 99%
“…However, parkinsonism is associated with relatively minor changes in firing in the basal ganglia receiving portion of the thalamus. [248][249][250][251][252] Whereas traditional models predict that interventions aimed at the basal ganglia-receiving portion of the ventral motor thalamus "should" impact bradykinesia or akinesia, these predictions have not been confirmed in parkinsonian animals or human patients with the disease (e.g., see an earlier work). 35 These findings suggest that the branching GPi projections to brainstem nuclei, such as the PPN, 253,254 may be more important for the development of bradykinesia or akinesia than traditionally assumed.…”
Section: Role Of Brainstem Nucleimentioning
confidence: 99%
“…2 E-H). Interestingly, it has been demonstrated that STN, GPi, and GPe stimulation, although producing similar behavioral improvement in motor signs, may impose different changes in the network (74,75,78,82,83), suggestive of the idea that the therapeutic mechanisms of DBS may vary depending on the target and location of the DBS lead within that target.…”
Section: Dbs and The Role Of Monkey Researchmentioning
confidence: 99%
“…This suggests that in Parkinson's disease higher-order correlations are relevant for motor symptoms, which offers some insight into the potential mechanisms by which deep-brain stimulation (DBS) might alleviate some of the motor symptoms such as rigidity and tremor. DBS in the STN and GPi has complex and diverse effects on the firing rate of neurons in SNr/GPi (Bar-Gad et al, 2004;Zimnik et al, 2015) and thalamus (Muralidharan et al, 2017). According to our model strong increases in SNr and GPi firing rates observed after STN DBS (Hashimoto et al, 2003;Maurice et al, 2003), would decrease the duration of the spontaneous pauses in the population activity ( Figure 3C).…”
Section: Effects Of Deep Brain Stimulationmentioning
confidence: 59%